Postural analysis of the forestry worker in sawmills of El Salto, Durango, Mexico - Aragón-Vásquez, Alondra Yareli; Silva-Lugo, Edwin Daniel; Nájera-Luna, Juan Abel; Méndez-González, Jorge; Hernández, Francisco Javier; de la Cruz-Carrera, Ricardo (Instituto de Ecología, A.C., 2019)
The work in the sawmill industry is physically demanding because it is performed under unhealthy body postures that generate musculoskeletal injuries and its study requires risk assessment tools to identify the most serious. In the sawmills of El Salto, Durango, Mexico, the level of risk of the work positions in people is unknown; therefore, the objective of this study was to perform a postural analysis in 15 workplaces. From 7.5 hours of video that considered effective work in the workplace, 900 still images were obtained at 30-second intervals to analyze them using the OWAS method. The global index of postural risk was estimated and contingency tables and association tests between categorical variables of chi square were elaborated. The results showed a frequency of postures of 48% with risk levels 2, 3 and 4, indicating actions for postural correction for risks 2 and 3 as well as immediate modifications for the 4. The global risk index was established at 166 points cataloged as minimum. By workplace, the workers in the manual logs handling and manual stacking and carriage of lumber are the most susceptible to present injuries with global risk indexes above 200 points. By body area, 43% of the positions of the back and 40% of the legs are in a level risk 2 considered as not harmful, and 100% of the positions of the arms resulted with a level risk 1 not requiring any modification.